CURCUMINOIDS: RECOVERY, PROPERTIES AND APPLICATION REPORT 1. RECOVERY OF CURCUMINOIDS AND THEIR PHYSICAL AND CHEMICAL PROPERTIES - M. A. Kapustin; A. S. Chubarova; S. V. Lodygina; A. D. Lodigin; I. A. Evdokimov; А. V. Yantsevich; V. P. Kurchenko (Современная наука и инновации, 2023)
HPLC method of curcuminoids (curcumin, demetoxycurcumin, bis-demetoxycurcumin) qualitative and quantitative analysis is developed. The protocol of curcuminoids additive preparation recovery from vegetative raw material (Curcuma longa L.) by different extractants is described. Conditions of individual curcuminoids preparative isolation are presented. Physical and chemical properties of derived substances are studied. Basic block diagram of curcuminoids manufacturing from vegetative raw material is developed.